Synthesis and evaluation of the anticonvulsant activities of some 5-(4-substitutedbenzylidene)-6-methyl-4,5-dihydropyridazine-3(2H)-ones - (:unkn) unknown (My University, 2004)
In this study, starting from 3-benzylidene-4-oxopentanoic add derivatives (1a-e), having 5-benzylidene-6-methyl-4,5-dihydropyridazine-3(2H)-one (2a-e) structure and their ester (3a-e), hydrazide (4a-e) and acetic acid (5a-e) derivatives were synthesized. The physical properties and UV absorptions of the five starting compounds (1a-e) and twenty target compounds (2a-5e) were determined. Their chemical structures were achieved by IR and 1H-NMR spectral data. Additionally, elemental analysis data of the new compounds (1b, 2b, 3b, 4b, 5b, 3c, 4c, 5c, 2e, 3e, 4e and 5e) were done to identify the structures. Anticonvulsant activities of the target compounds (2a-5e) were screened by pentylenetetrazole seizure model. It was observed that compound 2a showed an anticonvulsant effect similar to ethosuximide concerning the seizure grade.
Keywords: 4,5-dihydropyridazine-3(2H)-one; 6-oxo-5,6-dihydropyridazinylacetate; 6-oxo-5,6-dihydropyridazinylacetic acid; 6-oxo-5,6-dihydropyridazinylacetohydrazide; Anticonvulsant activity